Anthropometric and Physical Mapping of Elementary School Athletes: Implications for Swimming Talent - Maulidin, Maulidin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
Talent identification is a critical component of long-term athlete development, particularly in swimming, where performance is strongly influenced by anthropometric and biomotor characteristics. Nevertheless, talent selection at the elementary school level often relies on subjective observation, limiting objectivity and predictive accuracy. This study aimed to map the anthropometric and biomotor profiles of elementary school–aged athletes participating in the UAFC 2025 Championship and to identify dominant physical characteristics associated with competitive performance. A quantitative descriptive design was applied involving 15 young athletes. Anthropometric variables and biomotor capacities, including speed, agility, explosive power, and aerobic endurance, were assessed using standardized measurement instruments. Data were analyzed using descriptive statistics, k-means cluster analysis, and correlational analysis. The results revealed two distinct physical profiles: Type A (Competitive Ideal), characterized by favorable anthropometric dimensions and balanced biomotor capacities, and Type B (Endurance-Dominant), characterized by moderate body dimensions and superior cardiorespiratory endurance. Athletes classified as Type A achieved a higher proportion of medals, while aerobic endurance showed a strong and significant association with competitive ranking. These findings highlight the multidimensional nature of performance in young swimmers. In conclusion, integrating anthropometric and biomotor profiling provides an evidence-based framework for early talent identification and supports more objective selection and individualized training pathways in youth swimming.